THE FIRST FERMI MULTIFREQUENCY CAMPAIGN ON BL LACERTAE: CHARACTERIZING THE LOW-ACTIVITY STATE OF THE EPONYMOUS BLAZAR - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2011)
We report on observations of BL Lacertae during the first 18 months of Fermi LAT science operations and present results from a 48 day multifrequency coordinated campaign from 2008 August 19 to 2008 October 7. The radio to gamma-ray behavior of BL Lac is unveiled during a low-activity state thanks to the coordinated observations of radio-band (Metsahovi and VLBA), near-IR/optical (Tuorla, Steward, OAGH, and MDM), and X-ray (RXTE and Swift) observatories. No variability was resolved in gamma rays during the campaign, and the brightness level was 15 times lower than the level of the 1997 EGRET outburst. Moderate and uncorrelated variability has been detected in UV and X-rays. The X-ray spectrum is found to be concave, indicating the transition region between the low- and high-energy components of the spectral energy distribution (SED). VLBA observation detected a synchrotron spectrum self-absorption turnover in the innermost part of the radio jet appearing to be elongated and inhomogeneous, and constrained the average magnetic field there to be less than 3 G. Over the following months, BL Lac appeared variable in gamma rays, showing flares (in 2009 April and 2010 January). There is no evidence for the correlation of gamma rays with the optical flux monitored from the ground in 18 months. The SED may be described by a single-zone or a two-zone synchrotron self-Compton (SSC) model, but a hybrid SSC plus external radiation Compton model seems to be preferred based on the observed variability and the fact that it provides a fit closest to equipartition.
CRIS-Team WoS Importer:2020-01-15